PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PENARIKAN KESIMPULAN LOGIKA MATEMATIKA DI KELAS X SMA GPID PALU - Paembonan, Roni Dudung; Abd. Hamid, Abd. Hamid; Rochaminah, Sutji (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The Objective of this research was to obtain the description about application of cooperative learning of Numbered Heads Together (NHT) to improve studentâs learning outcomes on inference of mathematic logic in class X SMA GPID Palu. This research was class action research, that refered to the research design of Kemmis and Mc. Taggart. The results of this research indicating that cooperative learning of NHT can improve studentâs learning outcomes on inference of mathematic logic, by following the phases, those are: (1) phase convey the purpose and motivating student, (2) phase presentation of information, (3) phase organizing study groups and numbering, (4) phase questioning, (5) phase heads together, (6) phase answering.